(untitled) (International journal of medical sciences, 2025)
Post-traumatic encephalopathy (PTE) in children is a multifactorial pathological condition that develops following traumatic brain injury and is characterized by both acute and long-term disturbances of central nervous system function. Its pathogenesis is driven by the interaction between primary mechanical damage and a cascade of secondary neurobiological processes, including excitotoxicity, mitochondrial dysfunction, ionic imbalance, oxidative stress, blood–brain barrier disruption, and neuroinflammation. Age-related features of the developing brain—such as incomplete myelination, high metabolic demand, and enhanced neuroplasticity—determine both increased vulnerability to traumatic injury and potential for recovery. Long-term consequences of pediatric PTE may manifest as cognitive, behavioral, and emotional impairments that negatively affect quality of life and neuropsychological development. A deeper understanding of the underlying pathophysiological mechanisms is essential for improving diagnostic approaches, prevention, and the development of effective neuroprotective strategies in pediatric neurology.